2022
DOI: 10.1037/ocp0000315
|View full text |Cite
|
Sign up to set email alerts
|

Putting workplace bullying in context: The role of high-involvement work practices in the relationship between job demands, job resources, and bullying exposure.

Abstract: Previous research has demonstrated the crucial association between employee stressors and workplace bullying. In this article, we argue that a nurturing organizational context will protect employees from exposure to workplace bullying and will interact with individual demands and resources known to have effect on exposure to bullying in the workplace. In specific, we look at high-involvement work practices (HIWPs)-which include participation, information-sharing, competence development, and rewards. Multilevel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 140 publications
0
7
0
1
Order By: Relevance
“… Taris (2022) further argued that bullying is a time-dependent and contextual phenomenon. Initially, the preparator shows mild aggression that turns into hard-line aggression with time to become more explicit ( Leymann, 1990 ; Vranjes et al, 2022a ). Various studies explored the adverse effects of such regular exploitations from several perspectives, such as post-traumatic stress ( Mikkelsen and Einarsen, 2002 ), anxiety ( Rai and Agarwal, 2018 ), turnover intentions ( Djurkovic et al, 2008 ), strain and wellbeing ( Rai and Agarwal, 2018 ), depression and propensity to leave ( Naseer et al, 2016 ), exhaustion and weak health ( Hauge et al, 2007 ), isolation within group/teams ( Samnani and Singh, 2012 ) and deviant work behaviour ( Naseer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… Taris (2022) further argued that bullying is a time-dependent and contextual phenomenon. Initially, the preparator shows mild aggression that turns into hard-line aggression with time to become more explicit ( Leymann, 1990 ; Vranjes et al, 2022a ). Various studies explored the adverse effects of such regular exploitations from several perspectives, such as post-traumatic stress ( Mikkelsen and Einarsen, 2002 ), anxiety ( Rai and Agarwal, 2018 ), turnover intentions ( Djurkovic et al, 2008 ), strain and wellbeing ( Rai and Agarwal, 2018 ), depression and propensity to leave ( Naseer et al, 2016 ), exhaustion and weak health ( Hauge et al, 2007 ), isolation within group/teams ( Samnani and Singh, 2012 ) and deviant work behaviour ( Naseer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace mistreatment involves manipulation, which is tied to organizational setting (Gul et al, 2019;Verdasca, 2010;Vranjes et al, 2022). Silence or manipulation characterize workplace mistreatment communication, as does judgmentalism (Täuber, 2019).…”
Section: Towards a More Complex View Of Workplace Mistreatmentmentioning
confidence: 99%
“…Moreover, hospital administrators in Jordan should establish a safe, positive, ethical, and participative culture that increases the trust of employees, mainly during bullying incidents. Recently, Vranjes et al (2022) found that high-involvement work practices including participation, information-sharing, competence development, and rewards are negatively associated with bullying exposure. Although cyberbullying ranked last in the practice policymakers should address this type significantly.…”
Section: Conclusion Practical Implications and Future Researchmentioning
confidence: 99%